Purchase Intention of Eco-Fashion: The Influence of Social Media and Environmental Concern - Gusfi, Vira Aulia; Lukitaningsih, Ambar; Fadhilah, Muinah (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of environmental concern and social media influence on purchase behavior, with purchase intention of eco-fashion products as a mediating variable. A quantitative method using PLS-SEM was applied to 104 eco-fashion consumers in Yogyakarta. The results show that environmental concern significantly affects both purchase intention and behavior, while social media influence only significantly affects purchase intention. Purchase intention mediates both relationships. The findings provide theoretical support for the Theory of Planned Behavior and practical implications for marketers in promoting sustainable fashion consumption.